The interaction of synbiotic of the environment and the endoecosystem as one of the mechanisms of action of balneotherapy - Popovych, Igor L.; Zukow, Walery A.; Fil, Vitalii M.; Kovalchuk, Halyna Y.; Bryndzia, Iryna V.; Voloshyn, Olena R.; Kopko, Iryna Y.; Lupak, Oksana M.; Skrobach, Taras B. (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Drinking mineral waters are one of the environmental factors that affect the condition of the human body. Of particular interest are therapeutic waters of the Naftussya type, which contain autochthonous microbes and organic oil-like substances and can be considered as a kind of ecosystem. On the other hand, gastrointestinal tract also is an ecosystem that associates a resident microbiota and cells of various phenotypes lining the epithelial wall. We assumed that one of the mechanisms of the therapeutic effect of Naftussya water is the interaction of external and internal ecosystems. This article is the first in a series in support of the hypothesis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The object of clinical-physiological observation were residents of the city of Truskavets’ (21 men aged 24-67 years and 8 women 33-76 years) with chronic pyelonephritis in remission. The objects of study: leukocyturia, bacteriuria, components of microbiota, phagocytosis function of neutrophils, leukocytary adaptation index, plasma and urine electrolytes and nitrogenous metabolites. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The weekly use of bioactive Naftussya water from the Opaka deposit causes a favorable normalizing effect on the stool microbiota: it increases the reduced content of Bifidobacteria and Lactobacilli, instead it reduces the increased content of pathogenic strains of Escherichia coli, as well as Klebsiela and Proteus. Reduction of dysbacteriosis is accompanied by an increase in the reduced bactericidal capacity of blood neutrophils against E. coli and Staphylococcus aureus, and reduction of bacteriuria and leukocyturia. At the same time, the elevated level of creatinine in the plasma decreases, instead, the decreased levels of sodium and chloride increase. As expected, the daily diuresis and excretion of urea, creatinine, phosphates, calcium, magnesium and chloride increases, but not sodium and uric acid, the concentrations of which in the urine decrease. The described physiologically beneficial effects are interpreted as adaptogenic, which is confirmed by an increase in the reduced leukocyte adaptation index. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The healing effect of Naftussya bioactive water is the result of the interaction of external and internal ecosystems. The next article will consider the role of the nervous and endocrine systems in this interaction.